Autonomous dysfunction in patients with metabolic syndrome: heart rate variability study - D. A. Anichkov; N. A. Shostak; L. A. Kotlyarova; D. S. Ivanov (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To assess autonomous regulation of heart rhythm in metabolic syndrome (MS) patients and clinically healthy individuals, using heart rate variability (HRV) analysis. Material and methods. The main group included 23 MS patients, the control group – 22 healthy individuals. All participants underwent 24-hour Holter ECG monitoring, with temporal HRV analysis. Results. In MS patients, all HRV parameters were significantly lower than in healthy individuals (p<0.001). Nevertheless, after including mean 24-hour HR into analysis, the difference between examined HRV parameters became only borderline significant. Similar data was obtained for mean daytime HRV parameters; no difference for mean nighttime HRV parameters was detected after adjustment for HR and age. Conclusion. MS patients demonstrated autonomous dysfunction, manifested as relative sympathic hypertonus. Autonomous regulation correction can be performed with imidazoline receptor agonists.